2020
DOI: 10.3390/molecules25184129
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-Uptake Activity and Cytotoxicity of Diterpenes and Triterpenes Isolated from Lamiaceae Plant Species

Abstract: The prevalence of diabetes mellitus (DM), considered one of the most common metabolic disorders, has dramatically increased and resulted in higher rates of morbidity and mortality around the world in the past decade. It is well known that insulin resistance in target tissues and a deficiency in insulin secretion from pancreatic β-cells are the main characteristics of type 2 diabetes. The aim of this study was the bio-evaluation of compounds isolated from three selected plant species: namely, Salvia africana-lu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In this regard, our laboratory study showed that the administration of catechin isolated from C. fistula to diabetic rats upregulated the expression of GLUT4 mRNA and protein. Similar studies revealed the hypoglycemic effects of cucurbitane triterpenoid isolated from bitter melon on GLUT4 translocation in the L6 muscle cells and 3T3-L1 adipocytes though activation of the AMPK pathway, as well as those of triterpenes isolated from Lamiaceae plant species in 3T3-L1 adipocytes through activation of the PI3K pathway [36,37].…”
Section: Discussionmentioning
confidence: 55%
“…In this regard, our laboratory study showed that the administration of catechin isolated from C. fistula to diabetic rats upregulated the expression of GLUT4 mRNA and protein. Similar studies revealed the hypoglycemic effects of cucurbitane triterpenoid isolated from bitter melon on GLUT4 translocation in the L6 muscle cells and 3T3-L1 adipocytes though activation of the AMPK pathway, as well as those of triterpenes isolated from Lamiaceae plant species in 3T3-L1 adipocytes through activation of the PI3K pathway [36,37].…”
Section: Discussionmentioning
confidence: 55%
“…The dHL-60 cells (1 × 10 5 ) were pretreated with Dex or PBS for 1 h and stimulated with GM-CSF for 4 h. The cell viability was assessed as previously described [ 45 , 46 , 47 , 48 , 49 ].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the number of people with T2DM is predicted to rise from 405 million in 2018 to 510 million by 2030 [5]. Peripherally, insulin promotes blood glucose uptake in the skeletal muscles and adipose cells, which helps to maintain glucose homeostasis [6]. Type 2 diabetes, on the other hand, is marked by insulin resistance in key target tissues such as the liver, skeletal muscles and adipose tissues, resulting in impaired glucose uptake and postprandial hyperglycemia.…”
Section: Introductionmentioning
confidence: 99%